A green printed veneer sheet
Patent Information
- Application Number
- CN202410658814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing particleboards still release relatively high amounts of formaldehyde after surface treatment, which affects environmental performance.
Through the preparation of modified impregnated film paper, acetic acid solution, chitosan and zinc chloride aqueous solution are used to treat the decorative base paper, and aldehyde-removing emulsion and modifying additives, including anatase nano-titanium dioxide, are added to the melamine impregnating solution to reduce the Formaldehyde release.
It effectively reduces the formaldehyde release of printed decorative panels, improves the environmental performance of the panels, and further improves moisture resistance through photocatalysis and oxidation reactions.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plate production, and in particular relates to a green printed veneer plate. Background Art
[0002] Particleboard is one of the man-made board products. It is made of wood raw materials through planing, gluing, assembly and hot pressing. It has the advantages of uniform structure and good processability and is widely used in the field of furniture decoration. However, particleboard also has the problems of rough surface, poor moisture resistance and high free formaldehyde.
[0003] Surface treatment of particleboard can effectively improve the physical and chemical properties of particleboard. Common surface treatment methods include surface mechanical processing, coating and cladding decoration. Specifically, surface mechanical processing can remove the pre-cured layer on the surface of particleboard and can also accurately control the thickness of the board, but surface mechanical processing alone cannot improve its environmental performance; although coating can give the board certain special properties, it also has little effect on reducing the release of harmful gases; cladding decoration is to press decorative materials on the surface of particleboard. This method can not only beautify the substrate and protect the strength, but also slow down or inhibit the release of harmful gases. It is an important way to improve the surface performance and environmental performance of particleboard. The cladding decoration treatment usually produces impregnated film paper veneer board material, uses melamine impregnation liquid to dip-coat the decorative paper, and then hot-presses it on both sides of the particleboard substrate to complete the cladding decoration treatment. However, the main component of the existing melamine impregnation liquid is melamine formaldehyde resin, resulting in a high formaldehyde release of the printed veneer board produced in the end. Summary of the invention
[0004] The purpose of the present invention is to provide a green printed veneer board material, by improving the impregnation glue solution of the decorative base paper in the veneer board material, so as to reduce the formaldehyde emission of the finally produced printed veneer board material, and achieve the purpose of green environmental protection.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A green printed veneer board material, comprising a particle board substrate;
[0007] Both sides of the particleboard substrate are hot-pressed with modified impregnated adhesive film paper;
[0008] The modified impregnated film paper is prepared by impregnating the modified decorative paper with melamine impregnation liquid;
[0009] The modified decorative paper is prepared by the following steps:
[0010] S1. Add chitosan to a 1% acetic acid solution, stir for 15-20 minutes, let stand until there are no bubbles to obtain a suspension, place the suspension in an ice water bath, add a 13%-15% zinc chloride aqueous solution thereto, stir for 15-20 minutes to obtain a mixed solution, immerse the decorative base paper in the mixed solution, treat at 60-80° C. for 2-3 hours, take out the decorative base paper, dry it, and then immerse the decorative base paper in a 10% stearic acid ethanol solution, treat it for 30 minutes, take out the decorative base paper, and dry it to obtain a modified decorative base paper;
[0011] S2. Applying a sizing agent on the surface of the modified decorative base paper, and after it is completely dried, processing the modified filter paper into a cardboard to produce a modified decorative paper.
[0012] Furthermore, in step S1, the usage ratio of the acetic acid solution, chitosan and zinc chloride aqueous solution is 300 mL: 20-25 g: 75 mL.
[0013] Further, the sizing agent is prepared by the following steps:
[0014] A1. Add cationic starch and carboxymethyl cellulose to deionized water, stir until the solid is completely dissolved, heat to 95°C, stir until the solution turns gray, add rosin and cationic emulsifier, stir until the solid is completely dissolved, and keep warm at 90°C for 30-60 minutes to obtain a mixed solution;
[0015] A2. Add the formaldehyde-removing emulsion and the modifying aid to the mixed solution, stir until dissolved, then add paraffin and surfactant, stir until dissolved, keep warm at 80-90°C for 10 minutes, cool to 60-70°C, add 15%-20% zirconium hydroxide solution, stir for 10 minutes, let stand, cool to room temperature, discharge, and obtain the sizing agent.
[0016] Furthermore, in step A1, the mass ratio of the deionized water, cationic starch, carboxymethyl cellulose, rosin and cationic emulsifier is 50:1-2:1-3:1:4.
[0017] Furthermore, the mass ratio of the mixed solution, the formaldehyde-removing emulsion, paraffin, the surfactant and the stabilizer in step A2 is 60-65:4:2:0.5-1:0.3-0.4.
[0018] Furthermore, the melamine impregnation solution is composed of the following raw materials in weight percentage:
[0019] Melamine formaldehyde resin 80%-85%;
[0020] Penetrant 2%-4%;
[0021] Leveling agent 1%-2%;
[0022] The balance is pure water.
[0023] Furthermore, the penetrant is one of sulfated castor oil, sodium alkyl sulfonate, and fatty acid polyethylene ether.
[0024] Furthermore, the leveling agent is one of polydimethylsiloxane, Efka 3777 leveling agent, and Digo 1484.
[0025] Furthermore, the green printed facing sheet material is prepared by the following steps:
[0026] The prepared impregnated adhesive film paper is hot-pressed and laminated on both sides of the particleboard substrate. The hot-pressing temperature is 130-135° C., the hot-pressing pressure is 0.60-0.80 MPa, and the hot-pressing time is 5-6 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a green printed veneer board.
[0027] Furthermore, the moisture content of the substrate is 6.2%-7.0%.
[0028] Furthermore, the thickness of the substrate is 15.5-17.0 mm.
[0029] Beneficial effects of the present invention:
[0030] The present invention provides a green printed veneer board material, which achieves the purpose of reducing the formaldehyde emission of the printed veneer board material by improving the impregnating glue solution of the decorative base paper in the veneer board material. Specifically, the present invention provides a modified resin glue, which achieves the purpose of reducing the formaldehyde emission of the printed veneer board material by adding a formaldehyde-removing emulsion and a modification auxiliary agent to a melamine formaldehyde resin.
[0031] Among them, the addition of aldehyde-removing emulsion has the following advantages:
[0032] The formaldehyde-removing emulsion prepared by the invention contains active amino groups, which can react irreversibly with free formaldehyde in the impregnating glue solution to achieve the purpose of degrading formaldehyde.
[0033] Among them, the addition of modification additives has the following advantages:
[0034] The modified auxiliary agent prepared by the present invention contains anatase nano titanium dioxide, which has excellent photocatalytic performance under ultraviolet light environment. Under the excitation of ultraviolet light, anatase nano titanium dioxide will generate photogenerated carriers (photogenerated electrons and holes), which can react with oxygen and water in the air to obtain free radicals (-OH, -O 2 -), free radicals can catalyze the degradation of formaldehyde into small molecules such as carbon dioxide. This process requires the use of oxygen and water in the air, which can help solve the problem of poor moisture resistance of the particleboard substrate of the board material of the present invention. This process can reduce the impact of water molecules in the air on the particleboard.
[0035] The present invention forms a dense glue film on the surface of the decorative base paper by performing surface sizing treatment on the decorative base paper, which reduces the liquid absorption capacity of the paper on the one hand, and prevents the impregnation glue liquid from vertically penetrating from the paper on the other hand, and prevents the impregnation glue liquid from filling the gaps between the decorative base paper fibers, thereby reducing the formaldehyde release of the later veneer particleboard. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] The present invention selects a particle board with a thickness of 16 mm as the substrate material.
[0038] Example 1
[0039] Preparation of sizing agent:
[0040] A1. Add cationic starch and carboxymethyl cellulose to deionized water, stir until the solid is completely dissolved, heat to 95°C, stir until the solution is gray, add rosin and cationic emulsifier (model: HM-633A), stir until the solution is completely dissolved, and keep warm at 90°C for 30 minutes to obtain a mixed solution, wherein the mass ratio of deionized water, cationic starch, carboxymethyl cellulose, rosin and cationic emulsifier is 50:1:1:1:4;
[0041] A2. Add formaldehyde-removing emulsion to the mixed solution, stir until dissolved, then add paraffin and surfactant (Jiangsu Sixin Interface Agent Technology Co., Ltd.), stir until dissolved, keep warm at 80°C for 10 minutes, cool to 60°C, add 15% zirconium hydroxide solution, stir for 10 minutes, let stand, cool to room temperature, discharge, and obtain a sizing agent, wherein the mass ratio of the mixed solution, formaldehyde-removing emulsion, paraffin, surfactant and stabilizer is 60:4:2:0.5:0.3.
[0042] Example 2
[0043] Preparation of sizing agent:
[0044] A1. Add cationic starch and carboxymethyl cellulose to deionized water, stir until the solid is completely dissolved, heat to 95°C, stir until the solution is gray, add rosin and cationic emulsifier (model: HM-633A), stir until the solution is completely dissolved, and keep warm at 90°C for 50 minutes to obtain a mixed solution, wherein the mass ratio of deionized water, cationic starch, carboxymethyl cellulose, rosin and cationic emulsifier is 50:2:2:1:4;
[0045] A2. Add formaldehyde-removing emulsion to the mixed liquid, stir until dissolved, then add paraffin and surfactant (Jiangsu Sixin Interface Agent Technology Co., Ltd.), stir until dissolved, keep warm at 85°C for 10 minutes, cool to 65°C, add 18% zirconium hydroxide solution, stir for 10 minutes, let stand, cool to room temperature, discharge, and obtain a sizing agent, wherein the mass ratio of the mixed liquid, formaldehyde-removing emulsion, paraffin, surfactant and stabilizer is 62:4:2:0.8:0.4.
[0046] Example 3
[0047] Preparation of sizing agent:
[0048] A1. Add cationic starch and carboxymethyl cellulose to deionized water, stir until the solid is completely dissolved, heat to 95°C, stir until the solution is gray, add rosin and cationic emulsifier (model: HM-633A), stir until the solution is completely dissolved, and keep warm at 90°C for 60 minutes to obtain a mixed solution, wherein the mass ratio of deionized water, cationic starch, carboxymethyl cellulose, rosin and cationic emulsifier is 50:2:3:1:4;
[0049] A2. Add formaldehyde-removing emulsion to the mixed liquid, stir until dissolved, then add paraffin and surfactant (Jiangsu Sixin Interface Agent Technology Co., Ltd.), stir until dissolved, keep warm at 90°C for 10 minutes, cool to 70°C, add 20% zirconium hydroxide solution, stir for 10 minutes, let stand, cool to room temperature, discharge, and obtain a sizing agent, wherein the mass ratio of the mixed liquid, formaldehyde-removing emulsion, paraffin, surfactant and stabilizer is 65:4:2:1:0.4.
[0050] Example 4
[0051] Prepare a green printed veneer board material, including a particle board substrate;
[0052] Both sides of the particleboard substrate are hot-pressed with modified impregnated adhesive film paper;
[0053] The modified impregnated film paper is prepared by impregnating the modified decorative paper with melamine impregnation liquid;
[0054] The modified decorative paper is prepared by the following steps:
[0055] S1. Add chitosan to a 1% acetic acid solution, stir for 15-20 minutes, let stand until there are no bubbles to obtain a suspension, place the suspension in an ice water bath, add a 13%-15% zinc chloride aqueous solution thereto, stir for 15-20 minutes to obtain a mixed solution, immerse the decorative base paper in the mixed solution, treat at 60-80° C. for 2-3 hours, take out the decorative base paper, dry it, and then immerse the decorative base paper in a 10% stearic acid ethanol solution, treat it for 30 minutes, take out the decorative base paper, and dry it to obtain a modified decorative base paper;
[0056] S2. Applying a sizing agent on the surface of the modified decorative base paper, and after it is completely dried, processing the modified filter paper into a cardboard to produce a modified decorative paper.
[0057] The green printed veneer sheet is prepared by the following steps:
[0058] The prepared impregnated adhesive film paper is hot-pressed and laminated on both sides of the particleboard substrate. The hot-pressing temperature is 130-135° C., the hot-pressing pressure is 0.60-0.80 MPa, and the hot-pressing time is 5-6 min. After the hot-pressing is completed, it is cooled to room temperature to obtain a green printed veneer board.
[0059] Wherein, the moisture content of the substrate is 6.2%-7.0%.
[0060] Wherein, the thickness of the substrate is 15.5-17.0 mm.
[0061] The sizing agent in S2 is prepared according to the method of Example 1.
[0062] Example 5
[0063] The preparation steps of this embodiment are consistent with those of embodiment 4, except that the sizing agent in S2 is prepared according to the method of embodiment 2.
[0064] Example 6
[0065] The preparation steps of this embodiment are consistent with those of embodiment 4, except that the sizing agent in S2 is prepared according to the method of embodiment 3.
[0066] Comparative Example 1
[0067] A veneer board material, comprising a particle board substrate;
[0068] Both sides of the particleboard substrate are hot-pressed with modified impregnated adhesive film paper;
[0069] The modified impregnated film paper is prepared by impregnating decorative base paper with melamine impregnation liquid.
[0070] Comparative Example 2
[0071] A veneer board material, comprising a particle board substrate;
[0072] Both sides of the particleboard substrate are hot-pressed with modified impregnated adhesive film paper;
[0073] The modified impregnated film paper is prepared by impregnating decorative base paper with phenolic resin impregnation liquid.
[0074] Comparative Example 3
[0075] A veneer board material, comprising a particle board substrate;
[0076] Both sides of the particleboard substrate are hot-pressed with modified impregnated adhesive film paper;
[0077] The modified impregnated film paper is prepared by impregnating decorative base paper with modified amino resin impregnation liquid.
[0078] According to the above-mentioned Examples 4 to 6, and Comparative Examples 1 to 3, veneered particle boards were prepared. After obtaining different veneered particle boards, eight groups of samples were cut from the same veneer particle board, and balanced for 15 days at a temperature of (23±1)°C and a humidity of (50±5)%. Then, the physical and mechanical properties of the treated samples were tested with reference to GB / T17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels". That is, seven groups of samples were selected for: density, 2h water absorption thickness expansion rate, static bending strength and elastic modulus, surface bonding strength, internal bonding strength and screw holding force tests, and the test results are shown in Table 1.
[0079] The remaining group of samples were then tested for formaldehyde release. 3 The test was carried out in a climate chamber method, with the test chamber temperature at (23±0.5)°C and the relative humidity at (50±3)%. The test time was until the formaldehyde release reached a stable state. The test results are shown in Table 1:
[0080]
[0081]
[0082] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A green printed veneer sheet, characterized in that: Includes particleboard substrate; Both sides of the particleboard substrate are hot-pressed with modified impregnated adhesive film paper; The modified impregnated film paper is prepared by impregnating the modified decorative paper with melamine impregnation liquid; The modified decorative paper is prepared by the following steps: S1. Add chitosan to a 1% acetic acid solution, stir for 15-20 minutes, let stand until there are no bubbles to obtain a suspension, place the suspension in an ice water bath, add a 13%-15% zinc chloride aqueous solution thereto, stir for 15-20 minutes to obtain a mixed solution, immerse the decorative base paper in the mixed solution, treat at 60-80° C. for 2-3 hours, take out the decorative base paper, dry it, and then immerse the decorative base paper in a 10% stearic acid ethanol solution, treat it for 30 minutes, take out the decorative base paper, and dry it to obtain a modified decorative base paper; S2. Applying a sizing agent on the surface of the modified decorative base paper, and after it is completely dried, processing the modified filter paper into a cardboard to produce a modified decorative paper.
2. The green printed facing sheet material according to claim 1, characterized in that: The usage ratio of the acetic acid solution, chitosan and zinc chloride aqueous solution in step S1 is 300 mL: 20-25 g: 75 mL.
3. The green printed facing sheet material according to claim 1, characterized in that: The sizing agent is prepared by the following steps: A1. Add cationic starch and carboxymethyl cellulose to deionized water, stir until the solid is completely dissolved, heat to 95°C, stir until the solution turns gray, add rosin and cationic emulsifier, stir until the solid is completely dissolved, and keep warm at 90°C for 30-60 minutes to obtain a mixed solution; A2. Add the formaldehyde-removing emulsion and the modifying aid to the mixed solution, stir until dissolved, then add paraffin and surfactant, stir until dissolved, keep warm at 80-90°C for 10 minutes, cool to 60-70°C, add 15%-20% zirconium hydroxide solution, stir for 10 minutes, let stand, cool to room temperature, discharge, and obtain the sizing agent.
4. The green printed facing sheet material according to claim 3, characterized in that: The mass ratio of the deionized water, cationic starch, carboxymethyl cellulose, rosin and cationic emulsifier in step A1 is 50:1-2:1-3:1:
4.
5. The green printed facing sheet material according to claim 3, characterized in that: The mass ratio of the mixed solution, the formaldehyde-removing emulsion, paraffin, the surfactant and the stabilizer in step A2 is 60-65:4:2:0.5-1:0.3-0.
4.
6. The green printed facing sheet material according to claim 1, characterized in that: The melamine impregnation solution is composed of the following raw materials in weight percentage: Melamine formaldehyde resin 80%-85%; Penetrant 2%-4%; Leveling agent 1%-2%; The balance is pure water.
7. The green printed facing sheet material according to claim 6, characterized in that: The penetrant is one of sulfated castor oil, sodium alkyl sulfonate, and fatty acid polyethylene ether.
8. The green printed facing sheet material according to claim 6, characterized in that: The leveling agent is one of polydimethylsiloxane, Efka 3777 leveling agent, and Digo 1484.